Public education under siege - Katz, Michael B., 1939-2014; Rose, Mike (Michael Anthony) (EBL-Schweitzer, 2013)
This book argues for a democratic and egalitarian alternative to the test-driven, market-oriented core of current education reform. The essays in this text cover public policy, teacher unions, economic inequality, race, language diversity, parent involvement, and leadership.